Anatomy of biometric passports - Malčík, Dominik; Drahanský, Martin (Journal of biomedicine & biotechnology, 2012)
Travelling is becoming available for more and more people. Millions of people are on a way every day. That is why a better control over global human transfer and a more reliable identity check is desired. A recent trend in a field of personal identification documents is to use RFID (Radio Frequency Identification) technology and biometrics, especially (but not only) in passports. This paper provides an insight into the electronic passports (also called e-passport or ePassport) implementation chosen in the Czech Republic. Such a summary is needed for further studies of biometric passports implementation security and biometric passports analysis. A separate description of the Czech solution is a prerequisite for a planned analysis, because of the uniqueness of each implementation. (Each country can choose the implementation details within a range specified by the ICAO (International Civil Aviation Organisation); moreover, specific security mechanisms are optional and can be omitted).
Keywords: biometrická identifikace; Information Storage and Retrieval; identifikace na rádiové frekvenci - prostředky; záznamy jako téma; Humans; Česká republika; lidé; Records; cestování; ukládání a vyhledávání informací; Travel; Radio Frequency Identification Device; Czech Republic; Biometric Identification